STUDENT PERCEPTIONS OF ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Awal Kurnia Putra Nasution; Nurul Qomariyah Ahmad (Jurnal As-Salam, 2020)
Online learning has been chosen to be applied in all tertiary institutions in Indonesia; this also applies to IAIN Takengon. Student perception is one of the determinants of the success of the learning that is carried out. The purpose of writing this article is to find out how students' perceptions of online learning have been implemented and the factors that influence these perceptions. The research method used is an online survey using google form. The results showed that students' perceptions of online learning were not very good; this was caused by several factors, such as poor internet access, burdensome internet quota, difficulty communicating with lecturers, so students were not ready to use applications when online learning was carried out. There needs to be much improvement in the online learning system implemented; this indicates that universities are not ready to carry out online lectures.